FAKTOR YANG MENYEBABKAN OPINI AUDITOR ATAS LAPORAN KEUANGAN WAJAR DENGAN PENGECUALIAN - Anggraini, Novita; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out and to analyze the factor which makes auditor give fair with exceptionopinion on financial statement of the Municipality Government of Surabaya in 2010 and 2011. The method hasbeen carried out by using qualitative method whereas the data analysis technique has been carried out by usingdescriptive analysis. The researcher has been conducted the qualitative approach because she does not prove ahypothesis, but to find out financial statement of Municipality Government of Surabaya to obtain fair withexception opinion.It has been found from the result of this research that the financial statement of MunicipalityGovernment of Surabaya in 2010 and 2011 which has obtained fair with exception opinion has been caused bythe presentation of tax receivables has not been presented in conform with the amount of net value which can berealized, the revenue and expenditure which is related to the construction and the maintenance of utilitynetwork has not been run by using the local budget government mechanism, and the Municipality Governmentof Surabaya has not been able to show the evidence of the possession and ownership on ladder truck Firefightingminimum 52m based on the procurement in 2010.On the Financial Statement of Municipality Government ofSurabaya in 2010, the factor which makes fair with exception opinion has been obtained is more dominant to theweaknesses of internal control system. Meanwhile, in 2011 is more dominant on non-compliance factor to therules and regulations.Keywords:Fair with exception, disclosure, financial statement of municipality government.